Compared Position of Urination on Uroflowmetry and Post Void Residual in Patient with Benign Prostatic Hyperplasia (BPH) - Jongwannasiri, Mutita; Chintapanyakun, Teepatad; Viseshsindh, Wit (Journal of The Royal Thai Army Nurses, 2020)
This research aimed to compare the results of uroflowmetry parameters include maximum flow rate (Qmax), average flow rate (Qave), voided volume, voiding time and post-void residual urine (PVR) in the sitting and standing position in patients with BPH. Forty-four men with lower urinary tract symptoms (LUTS) due to BPH were enrolled in the one group pretest-posttest design study at urodynamics room in Ramathibodi hospital. The uroflowmetry were performed in both standing and sitting positions. The PVR were measured by bladder scan after each voiding. Uroflowmetry parameters and PVR values were compared between the two different voiding positions. The results showed that voided volume and voiding time were significantly increased in sitting position than the standing position. The PVR urine volume was significantly lower in the sitting position than the standing position. However, there were no significant differences between voiding positions regarding the Qmax and Qave in patients with BPH. Suggestion that the PVR seem to be affected by the voiding position (standing or sitting) in patient with BPH. Sitting position may be recommended for men with BPH to decrease PVR that may be reduce the risk of urinary tract infection.